As representações e práticas sociais acerca da gênese da Faculdade de Odontologia de Uberlândia (1966-1978) - Pereira, Wander (2006)
This present project is an interpretation of the presentations and social practices around the genesis of the Uberlândia´s Odontology Faculty, introduced in the field of Education History, specifically approaching the History of Educational Institutions. It has as a general objective, to aprehend the practices and the social representations, as well as apropriation constituted during the first times of Odontology School in Uberlândia (1966-1978). In an specific form, the contextual characteristics were interpreted according to the introduction of the School, analysing its structures, the relationship between the School and the community, the meanings and the practices done by the agents of Odontology School. The period that was used in this resource begins at 1966, year when the Odontology School was legally created, until 1978, year in what it constituted its federalization, together with the other courses at the Federal University, joining the Uberlândia´s Federal University. As far as is concerns to the researches sources, the priority was the ones which consisted in the archives of the Odontology School. Had been also used oral sources and bibliographies to the History of the Education, the History of the Pertaining to school Institutions and the ones that deal with the context of the Military dictatorship, where the cut period had been inserted. The proposed methodology refered to a guided interpretation: a) for the appropriation concepts, social practical representations brought by Roger Chartier, b) by the multidimensionality brought by the interdisciplinary of the interpretative modality indicated by Justino Magalhães, c) by the valuation of the regional and local singularities and specifities in the organization suggested by Ester Buffa and Paolo Nosella, d) by the use of the Oral History as a rich tecnique of the nowadays historiography.With the use of these new paradigms as theoretical-methodological referencials, the new historiography, characterized by a new renovation in the epistmological and hermeneutical situations, it had originated a widening of the problematics in Education History, also due to thematic inovations which increased the ways of questioning, investigating, aprehending and interpreting the diversity of historical contexts, creating a possibility of studying the genesis of the Uberlândia´s Odontology Faculty. The story of creation of the Uberlândia´s Odontology Faculty had been investigated, guided by this new historiography and being practised by great part of the historians who belong to the group of History and Historiography universities.It was possible to allow to the agents that participate of the construction process of the Uberlândia´s Odontology School identify and see themselves as historical subjects in the constitution of this Educational Institution in Uberlândia. The result of this text indicates that the genesis of the Uberlândia´s Odontology Faculty is inserted in a proper moment of Brazil´s History, precisely, in the conjuntural period in which the monopolist capitalism had already been definately set in the country and, under the overpower of the Military Government, that used repression strategies and co-optation of social categories, in the attempt of keeping itself in command. According to the politics adopted by the Military, expansion and interiorization practices had appeared in High School Education in Brazil, and also the creation of the Uberlândia´s Odontology Faculty.